2020
DOI: 10.3390/polym12010133
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Field-Assisted Gene Delivery from Polyelectrolyte Multilayers

Abstract: To sustain gene delivery and elongate transgene expression, plasmid DNA and cationic nonviral vectors can be deposited through layer-by-layer (LbL) assembly to form polyelectrolyte multilayers (PEMs). Although these macromolecules can be released for transfection purposes, their entanglement only allows partial delivery. Therefore, how to efficiently deliver immobilized genes from PEMs remains a challenge. In this study, we attempt to facilitate their delivery through the pretreatment of the external electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The use of light sensitive materials (mainly to low intensity UV radiation or near infrared radiation) on the fabrication of LbL capsules have also allowed the transport of the nanocapsules to a specific target, which open important possibilities for designing materials with specific targeting abilities [369]. Cheng et al [370]demonstrated that the application of an electrical field allows triggering the release of gene material (DNA) from its electrostatically assembled multilayers with PEI. The next step for the application of LbL capsules is the fabrication of smart systems enabling the triggering of the release as result of their expose to several stimuli, which provides the bases for an appropriate mimicking of the natural systems [361,364].…”
Section: Layer-by-layer Materials For Encapsulationmentioning
confidence: 99%
“…The use of light sensitive materials (mainly to low intensity UV radiation or near infrared radiation) on the fabrication of LbL capsules have also allowed the transport of the nanocapsules to a specific target, which open important possibilities for designing materials with specific targeting abilities [369]. Cheng et al [370]demonstrated that the application of an electrical field allows triggering the release of gene material (DNA) from its electrostatically assembled multilayers with PEI. The next step for the application of LbL capsules is the fabrication of smart systems enabling the triggering of the release as result of their expose to several stimuli, which provides the bases for an appropriate mimicking of the natural systems [361,364].…”
Section: Layer-by-layer Materials For Encapsulationmentioning
confidence: 99%
“…Positively and negatively charged polyelectrolytes can be alternately adsorbed via electrostatic adsorption to fabricate a polyelectrolyte multilayer (PEM) film; this is referred to as layer-by-layer (LbL) technology [29,30]. PEMs with controlled loading and release profiles has been experimentally used to deliver growth factors [31,32], DNA molecules [33,34], RNA molecules [35,36], etc.…”
Section: Introductionmentioning
confidence: 99%
“…We know that positively and negatively charged polyelectrolytes can be alternately adsorbed via electrostatic adsorption, called the layer-by-layer (LbL) technology, to fabricate the polyelectrolyte multilayer (PEM) film [27,28]. PEM with controlled loading and release profile has been experimentally used to deliver growth factors [29,30], DNA molecules [31,32], RNA molecules [33,34], etc. Here it is proposed that CS-antimiR-138 NPs and hyaluronic acid (HA, a commonly used polyanion in LbL) can be used to PEM-functionalize the Ti bone implant for sustainable antimiR-138 delivery and consequently augmented osseointegration.…”
Section: Introductionmentioning
confidence: 99%